Clinical outcomes of gemcitabine-loaded callispheres drug-eluting beads for patients with advanced and inoperable lung cancer: A case series study - Bi, Yonghua; Zhang, Bo; Ren, Jianzhuang; Han, Xinwei; Wu, Wenze (Frontiers in Pharmacology, 2022)
Aim: Drug-eluting beads transarterial chemoembolization (DEB-TACE) has not been widely used in patients with advanced and inoperable lung cancer. We aimed to report the preliminary outcomes of DEB-TACE with gemcitabine-loaded CalliSpheres beads for patients with advanced and inoperable lung cancer. Methods: From November 2017 to October 2021, 37 patients (29 males, mean age 64.7±10.3 years) with advanced and inoperable lung cancer underwent DEB-TACE with gemcitabine-loaded CalliSpheres beads. The primary endpoint was overall response rate, and the secondary endpoints were overall survival and progression-free survival. Results: A total of 54 sessions of DEB-TACE were performed in 37 patients, with a technique success rate of 100%. Fourteen patients received a second session of DEB-TACE. The mean follow-up time was 18.7±11.9 months. After 1, 3, and 6 months, overall response rate and disease control rate were 27.8% and 91.7%, 25.8% and 74.2%, 32.1% and 67.9%, respectively. The median progression-free survival was 8.8 months (95%CI 7.5, 12.5 months). The 3-, 6- and 12- month progression-free survival rates were 67.1%, 57.0% and 30.1%, respectively. The median overall survival was 10.0 months (95%CI 4.5, 13.1 months). The 3-, 6- and 12- month overall survival rates were 88.5%, 72.7% and 40.9%, respectively. Minor complications were observed in 14 patients (37.8%), with no procedure-related deaths or severe adverse events. Conclusion: DEB-TACE with gemcitabine-loaded CalliSpheres beads is a safe, feasible and effective treatment strategy for patients with advanced and inoperable lung cancer.